Biofuels in sustainable bioeconomy - Krasuska, Ewa; Rogulska, Magdalena (Studia Ecologiae et Bioethicae, 2017)
Transportation biofuels have been promoted by supportive policies and initially get public acceptance. However, over time many negative consequences raised controversies over conventional biofuels produced from food and feed crops. Advanced biofuels from feedstock not competing with food production are expected to have an important role in the new bioeconomy sector based on sustainable biomass production and conversion into a wide spectrum of added-value products. Biofuels should be mainly produced from wastes and residues. Biorefineries producing biofuels and bioproducts have a critical role in the industrial production of sustainable bioeconomy.